Efisiensi Biosorpsi Logam Fe Menggunakan Sisa Media Hidup Jamur Coprinus Comatus Pada Air Gambut - Santi Dwi Putri; Elvi Yenie; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Spent mushroom substrate, a renewable bio-waste from mushroom-growing industry, was used as a biosorbent to remove ion Fe metal in peat water. The purpose of this study was to determine metal removal efficiency of Fe in the peat water. Fixed variables used in this study is the stirring speed of 120 rpm and a contact time of 60 minutes. For independent variables used consisted of adsorbent mass variation of 0,1; 0,3; 0,5; 0,7; 0,9 g and a particle size variation 60, 100 and 140 mesh. The results showed highest removal efficiency of Fe metal concentration on peat water treatment by biosorption onto Coprinus comatus spent mushroom substrate at mass of biosorbent 0,9 g with a particle size of 140 mesh, with removal efficiency for fe metal concentration and color respectively amounted to 88,31%. Keywords: Biosorption, spent mushroom substrate, mass variation, Fe, peat water